FORECASTING EKSPOR RUMPUT LAUT MENGGUNAKAN ANALISIS TREND - Nabillah, Faradiba; Hazimah, Hazimah; Reza, Widya; Wahyu Aranski, Alvendo; Dwiakila Ramadhan , Achiles (LPPM Universitas Bina Bangsa, 2024)
Batam City is located in the Riau Islands Province, Indonesia, known as a strategic free trade area with rapidly growing industrial, trade, maritime and fisheries sectors, especially seaweed cultivation. Seaweed has high economic value and global demand, used as food and raw materials for the cosmetics, pharmaceutical and biotechnology industries. Batam's ideal geographical conditions support the growth of seaweed, with the support of local government policies and cultivation technology. However, challenges such as inadequate infrastructure, limited access to technology must be overcome to increase exports. On the other hand, competition with other neighboring seaweed countries such as Singapore, Vietnam and Thailand is also a challenge. These countries have already developed their seaweed industries well, including in terms of technology, product quality and international marketing networks. Batam needs to adopt innovative and efficient strategies and international cooperation to optimize this potential. With these problems, it is interesting to see the seaweed export forecast in Batam City. Is there an increase or decrease? So the purpose of this study is to describe the best model used in predicting seaweed export volume and describe the results of seaweed export volume predictions in Batam City in 2024 - 2025. The research method is quantitative using Trend analysis. The results of the study show that the best model used is the Quadratic trend model because it has the smallest MAPE, MAD and MSE values ​​compared to other models. Meanwhile, the results of seaweed export forecasts from Batam City continue to experience a significant increase in 2024 - 2025.